1985
DOI: 10.1161/01.cir.71.3.535
|View full text |Cite
|
Sign up to set email alerts
|

Alternative diagnostic strategies for coronary artery disease in women: demonstration of the usefulness and efficiency of probability analysis.

Abstract: Alternative strategies using conditional probability analysis for the diagnosis of coronary artery disease (CAD) were examined in 93 infarct-free women presenting with chest pain. Another group of 42 consecutive female patients was prospectively analyzed. For this latter group, the physician had access to the pretest and posttest probability of CAD before coronary angiography. These 135 women all underwent stress electrocardiographic, thallium scintigraphic, and coronary angiographic examination. The pretest a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
33
0
5

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(38 citation statements)
references
References 36 publications
(3 reference statements)
0
33
0
5
Order By: Relevance
“…This modification in the score derived from Framingham study database was made to integrate the chest pain criterion into the score and to adjust it to the characteristics of our patient population. This adjustment consisted of assigning different points to some of the risk factors and was based on a previous analysis (oral presentation, "V Simpósio Ibero-Americano de Cardiologia Nuclear", Florianópolis, December [5][6][7]2002). The final score used here ranges from -8 to 26 and is presented in Table 1.…”
Section: Collection and Classification Of Clinical And Epidemiologicamentioning
confidence: 99%
See 1 more Smart Citation
“…This modification in the score derived from Framingham study database was made to integrate the chest pain criterion into the score and to adjust it to the characteristics of our patient population. This adjustment consisted of assigning different points to some of the risk factors and was based on a previous analysis (oral presentation, "V Simpósio Ibero-Americano de Cardiologia Nuclear", Florianópolis, December [5][6][7]2002). The final score used here ranges from -8 to 26 and is presented in Table 1.…”
Section: Collection and Classification Of Clinical And Epidemiologicamentioning
confidence: 99%
“…Many investigators have demonstrated that the appropriate diagnostic applications of MPS are for patients who have an intermediate likelihood of disease (2)(3)(4)(5)(6). It has been suggested (6) that patients with a low likelihood of disease might not be tested or might simply undergo the TT.…”
Section: Introductionmentioning
confidence: 99%
“…A pesar de sus limitaciones en la mujer, se ha demostrado que la realización del ECG de esfuerzo reduce el número de pruebas diagnósticas sin que haya pérdida de precisión diagnóstica. De hecho, en sólo un 30% de las mujeres (aquellas en las que no se alcanzó el diagnóstico de CI o se lo excluyó con certeza) es preciso realizar otras pruebas 282 . Aunque aún está por definir la estrategia óptima para el diagnóstico de la CI en la mujer, el Grupo de Trabajo considera que no existe evidencia suficiente que haga recomendable sustituir en todas las mujeres en estudio por posible CI la ergometría convencional por las técnicas de imagen con estrés.…”
Section: Subgrupos Especiales Mujeresunclassified
“…Several research groups have published studies proposing algorithms aimed at establishing the best diagnostic strategy for CAD [8][9][10][11][12] .…”
mentioning
confidence: 99%
“…However, this is an expensive diagnostic method and must be utilized when the analysis of the clinical-epidemiological factors and results of the treadmill test do not significantly decrease the probability of obstructive coronary disease [8][9][10][11][12] . Therefore, it is important to define objective criteria, based on the analysis of clinical-epidemiological factors as well as the results of the treadmill test, which can be used to indicate the necessity of performing a myocardial perfusion scintigraphy.…”
mentioning
confidence: 99%